2018
DOI: 10.1002/adfm.201804427
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Ultrathin Bulk‐Heterojunction Organic Semiconductor Intermediary for High‐Performance Low‐Bandgap Perovskite Solar Cells with Low Energy Loss

Abstract: Mixed tin (Sn)-lead (Pb) perovskite is considered the most promising low-bandgap photovoltaic material for both pursuing the theoretical limiting efficiency of single-junction solar cells and breaking the Shockley-Queisser limitation by constructing tandem solar cells. However, their power conversion efficiencies (PCEs) are still lagging behind those of medium-bandgap perovskite solar cells (pero-SCs) due to their serious energy loss (E loss ). In this work, we used an ultra-thin bulkheterojunction (BHJ) organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 51 publications
4
97
0
Order By: Relevance
“…However, the proportion of crystal grains with sizes over 1 μm for perovskite film with Sn 4+ reduction seems slightly higher than that of the film without Sn 4+ reduction. Note that it has proven difficult to synthesize uniform, pinhole‐free, and Sn‐based perovskite thin films because Sn‐based perovskite films crystallized rapidly, the thickness of the (FASnI 3 ) 0.6 (MAPbI 3 ) 0.4 perovskite films prepared in this work is about 800 nm which is thicker than most previous reports of mixed Pb–Sn PSCs . It seems that the average grain size of the film is comparable with the film thickness.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…However, the proportion of crystal grains with sizes over 1 μm for perovskite film with Sn 4+ reduction seems slightly higher than that of the film without Sn 4+ reduction. Note that it has proven difficult to synthesize uniform, pinhole‐free, and Sn‐based perovskite thin films because Sn‐based perovskite films crystallized rapidly, the thickness of the (FASnI 3 ) 0.6 (MAPbI 3 ) 0.4 perovskite films prepared in this work is about 800 nm which is thicker than most previous reports of mixed Pb–Sn PSCs . It seems that the average grain size of the film is comparable with the film thickness.…”
mentioning
confidence: 64%
“…The crystallization of (FASnI 3 ) 0.6 (MAPbI 3 ) 0.4 films on PEDOT:PSS without and with Sn 4+ reduction has been evaluated by X‐ray diffraction (XRD) measurements, as shown in Figure S1, Supporting Information. The two XRD patterns show strong diffraction peaks at 14.1° and 28.3° corresponding to (110) and (220) preferred orientation . There is no obvious change in the XRD patterns of the perovskite films without and with Sn 4+ reduction, which indicates that Sn powder reduction has little effect on the crystallization of (FASnI 3 ) 0.6 (MAPbI 3 ) 0.4 perovskite films.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…And V eff is defined as V eff = V 0 – V app , where V 0 is the voltage when J ph = 0 and V app is the applied bias. The ratio of J ph / J sat can be used to estimate the charge collection efficiency under operation conditions, where J sat is the saturation photocurrent density . Under short circuit conditions, the J ph / J sat ratios were calculated to be 0.958 and 0.991 for the control and 2D/3D perovskite devices, respectively.…”
Section: Optimized Device Parameters For the Control And 2d/3d Perovsmentioning
confidence: 99%
“…Recently, Hayase and co‐workers reported low‐bandgap PSCs with a conduction band spike between the perovskite and electron transport layer (ETL), yielding a PCE of 17.6% . Xu et al reported mixed Sn‐Pb PSCs with a high PCE of 18.03%, achieved by incorporating an ultrathin organic semiconductor (PBDB‐T:ITIC) layer which sufficiently reduces the charge recombination at the front interface . More recently, Our group reported mixed Sn‐Pb PSCs with the highest PCE exceeding 19% through reducing the saturation current via Br incorporation .…”
Section: Introductionmentioning
confidence: 96%